Military fortifications of Almería during the Caliphate era (300-366 AH / 912-979 AD) (Journal of the College of Basic Education, 2025)
In this study, I will shed light on the military fortifications of the city of Almeria during the Caliphate era (300-366 AH / 912-979 AD), as military fortifications were among the most important defensive means used to protect and defend Islamic cities. These fortifications were represented in the construction of walls, towers, fortresses, and gates. The walls were a defensive fortification surrounding the city, equipped with towers. They played an important role in ensuring the city’s defense if the enemy tried to storm it. They were named after the cities heading towards them, and because of the importance of Almeria’s role as a naval base for the Andalusian fleet.